Homicide in contemporary Japan - Finch, Andrew J. (The British journal of criminology, 2001)
This paper examines patterns of homicide in Japan from 1989 to 1995 using data from the Heisei 00nen no Hanzai (Crime in 19XX [sic]). The analysis of these statistics produced the following patterns: men predominated as both victims and suspects; homicides typically occurred between friends or relatives; the most commonly used weapons were knives; and the most common motives were hatred and sexual jealousy. Comparisons were made with a similar study of statistics from the English and Welsh Homicide Index, and Japan was found to be similar except in two respects: the influence of boryokudan (organized criminal gangs), and the possibility that, in the case of parricide, much of the violence was directed by sons against their mothers